Ferroptosis and Autophagy-Related Genes in the Pathogenesis of Ischemic Cardiomyopathy - Zheng, Yue; Gao, Wenqing; Zhang, Qiang; Cheng, Xian; Liu, Yanwu; Qi, Zhenchang; Li, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background: Obesity plays an important role in T2DM and myocardial infarction (MI). Ferroptosis and ferritinophagy are related to metabolic pathways, such as fatty acid metabolism and mitochondrial respiration. We aimed to investigate the ferroptosis- and autophagy-related differentially expressed genes (DEGs) that might be potential targets for MI progression. Methods: GSE116250 was analyzed to obtain DEGs. A Venn diagram was used to obtain the overlapping ferroptosis- and autophagy-related DEGs. Enrichment pathway analysis was performed and the hub genes were obtained. Pivotal miRNAs, transcription factors and drugs with the hub genes interactions were also predicted. The MI mice model was constructed and qPCR analysis and single-cell sequencing were used to validate the hub genes. Results: Utilizing the limma package and Venn diagram, 26 ferroptosis-related and 29 autophagy-related DEGs were obtained. The list of ferroptosis-related DEGs was analyzed, which were involved in cellular response to toxic substance, cellular oxidant detoxification, and IL-17 signaling pathway. The list of autophagy-related DEGs were involved in regulation of autophagy, JAK-STAT signaling pathway and regulation of MAPK cascade. In the protein-protein interaction network, the hub DEGs, including IL-6, PTGS2, JUN, NQO1, NOS3, LEPR, NAMPT, CDKN2A, CDKN1A and Snai1, were obtained. After validation using qPCR analysis in the MI mice model and the single-cell sequencing, the 10 hub genes can be the potential targets for MI deterioration. Conclusion: The screened hub genes, IL-6, PTGS2, JUN, NQO1, NOS3, LEPR, NAMPT, CDKN2A, CDKN1A and Snai1, may be therapeutic targets for MI patients and prevent adverse cardiovascular events.